2005
DOI: 10.1097/01.ju.0000181830.43340.e7
|View full text |Cite
|
Sign up to set email alerts
|

Local Cost Structures and the Economics of Robot Assisted Radical Prostatectomy

Abstract: The inpatient costs of robotic assisted prostatectomy are volume dependent and cost equivalence with generalist radical retropubic prostatectomy is possible at higher volume RAP specialty centers. While RAP may be cost competitive with RRP at high cost hospitals or high volume RAP specialist centers, this procedure would exist at a cost premium to RRP in other practice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 13 publications
5
107
0
5
Order By: Relevance
“…Given the large number of men with prostate cancer, the effects of treatment have major public health implications, including patient counseling and financial costs. The existing studies comparing the costs of robotic and open radical prostatectomy, however, are limited in their scope, addressing only the costs of the procedure and initial hospital stay[40,41,42]. These studies do not consider subsequent costs from complications, treatment of side effects, or cancer recurrence, which may be substantial in this patient population.…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the large number of men with prostate cancer, the effects of treatment have major public health implications, including patient counseling and financial costs. The existing studies comparing the costs of robotic and open radical prostatectomy, however, are limited in their scope, addressing only the costs of the procedure and initial hospital stay[40,41,42]. These studies do not consider subsequent costs from complications, treatment of side effects, or cancer recurrence, which may be substantial in this patient population.…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
“…Cost studies by Lotan et al, Mouraviev et al, Scales et al, and Bolenz et al specifically compared RALP with ORP and reported higher operative costs with RALP, although comparisons were restricted to the costs of the procedure and the duration of initial hospitalization[40,41,42,43]. Scales et al reported that inpatient costs of RALP are volume dependent and that cost equivalence with ORP is possible at high-volume specialty centers; however, they do not report actual cost data[42].…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
See 1 more Smart Citation
“…Scales et al [51] showed the cost equivalence of RALRP with ORP based on 10 cases per week and cost superiority based on 14 cases per week in the United States. However, in many other countries, the high installation and maintenance costs of this technology prevent its widespread implementation, even in high-volume centres.…”
Section: The Learning Curve Issuementioning
confidence: 99%
“…Finally, the considerable costs make this a serious financial proposal by any hospital. 42 The cost includes the initial capital investment as well as the maintenance cost plus the use of any special laparoscopic instruments which have a programmed senescence ( Table 2 lays out potential set up and running costs in developing a robotic programme).…”
Section: Robotic Radical Prostatectomy: the Techniquementioning
confidence: 99%